Intellectual Diversities of Professor Khalil Siddiqui’s Poetry - Dr. Saima Abbas; Dr. Shahida Rasool (Zaban-o-Adab, 2024)
Khalil Siddiqui is a renowned linguist, critic, and poet. His linguistic prowess has been recognized at national as well as international level. As a Urdu Language literary luminary and critic he has proved his mettle in the prestigious literary circles. Despite his literary genius his self-effacing nature has prevented him from exposing himself through his poetic publications. That is the main reason why he could not showcase his prodigious talent in the shape of published works. This article therefore is an humble attempt to introduce the literary world to his creative genius and sublime poetry, In the shape of a compendium of his un published poetry and several poetic nuggets earlier published in different magazines and newspapers. In this publication an attempt has been made to throw fresh vignettes on Khalil Siddiqui’s poems and Ghazals highlighting the rich diversity of subjects covered in his poetry. The critical commentary on his works would enable the literary aficionados to understand his rich contribution to the development of a new tradition in Urdu Ghazal besides throwing light on the reasons why his creative contribution remained covered in a mist of obscurity.